INOVASI STRATEGI DALAM MENINGKATKAN KINERJA PEMASARAN DI ERA NEW NORMAL - Sutrisno, Eko; Suprianto, S; Kantari, Losa Ade (Fakultas Ekonomi dan Manajemen, 2025)
This study This study aims to determine innovative strategies to improve marketing performance in the new normal era. The type of this study was descriptive study which aims to formulate innovative strategies to improve marketing performance in the new normal era. The type of data used in this study was qualitative data obtained directly from primary sources, namely the owner and employees of the Moromesa Sumbawa Besar photo studio, totaling 5 people. The data used in this study were collected using structured interview techniques using a research instrument in the form of an interview guide. Data analysis in this study used SWOT analysis techniques. Based on the results of the SWOT analysis of internal and external factors found in the Moromesa Sumbawa Besar photo studio business, four alternative strategies can be formulated to improve marketing performance in the new normal era, namely the SO strategy (strengths-opportunities), WO strategy (weaknesses-opportunities), ST strategy (strengths-threats) and WT strategy (weaknesses-threats). The priority strategies that can be implemented to improve marketing performance in the new normal era include providing premium services or additional features, offering special promotions and providing more affordable special packages, providing facilities for family photo sessions, product photos, or creative photo sessions with various accessible props and backgrounds, and increasing studio visibility.